H2 as a fuel for flavin- and H2O2-dependent biocatalytic reactions. Issue 67 (22nd July 2020) - Al-Shameri, Ammar; Willot, Sébastien J.-P.; Paul, Caroline E.; Hollmann, Frank; Lauterbach, Lars
Abstract : We show that an O2 -tolerant hydrogenase is capable to regenerate flavins and to power flavin- and H2 O2 -dependent biocatalysts with H2 . Abstract : The soluble hydrogenase from Ralstonia eutropha provides an atom efficient regeneration system for reduced flavin cofactors using H2 as an electron source. We demonstrated this system for highly selective ene-reductase-catalyzed CC-double bond reductions and monooxygenase-catalyzed epoxidation. Reactions were expanded to aerobic conditions to supply H2 O2 for peroxygenase-catalyzed hydroxylations.